2015
DOI: 10.1371/journal.pone.0139720
|View full text |Cite|
|
Sign up to set email alerts
|

Obesity Resistance and Enhanced Insulin Sensitivity in Ahnak-/- Mice Fed a High Fat Diet Are Related to Impaired Adipogenesis and Increased Energy Expenditure

Abstract: ObjectiveRecent evidence has suggested that AHNAK expression is altered in obesity, although its role in adipose tissue development remains unclear. The objective of this study was to determine the molecular mechanism by which Ahnak influences adipogenesis and glucose homeostasis.DesignWe investigated the in vitro role of AHNAK in adipogenesis using adipose-derived mesenchymal stem cells (ADSCs) and C3H10T1/2 cells. AHNAK-KO male mice were fed a high-fat diet (HFD; 60% calories from fat) and examined for gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 52 publications
(52 reference statements)
2
29
1
Order By: Relevance
“…In our previous studies, we reported that Ahnak À/À mice exhibit enhanced insulin sensitivity, higher energy expenditure, upregulated lipolysis of white adipose tissues, and impaired adipocyte differentiation (8,16,17). Intriguingly, we found pneumocyte hyperplasia and lung tumor development in Ahnak À/À mice.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…In our previous studies, we reported that Ahnak À/À mice exhibit enhanced insulin sensitivity, higher energy expenditure, upregulated lipolysis of white adipose tissues, and impaired adipocyte differentiation (8,16,17). Intriguingly, we found pneumocyte hyperplasia and lung tumor development in Ahnak À/À mice.…”
Section: Introductionmentioning
confidence: 54%
“…25). AHNAK mRNA expression is highest in normal lung tissue among human tissues (15), and Ahnak mRNA was abundantly expressed in mouse lung tissue (26), suggesting physiologically important roles of Ahnak in lung. Collectively, these findings suggest that downregulation of Ahnak gene expression is associated with lung tumorigenesis.…”
Section: Ahnak Protein Expression Is Downregulated In Human Lung Cancersmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast to HDAC9, the peptidyl prolyl cis/trans isomerase Pin‐1 is upregulated during obesity (Nakatsu et al, ) and was shown through KO studies to be indispensable for adipogenesis in ASCs, which is consistent with observations that both genetic and chemical inhibition of Pin1 protected mice against diet‐induced obesity (A. Suzuki, Saeki, Ikuji, Uchida, & Uchida, ). Similar to Pin1, expression of the scaffolding protein Ahnak, which facilitates the Smad‐1 signaling required to induce PPARγ2 expression during adipogenesis, is also elevated in obesity and is upregulated during adipogenesis (J. Li, Yu, Pan, & Unger, ; J. H. Shin et al, ). Ahnak KO mice exhibited decreased fat mass and smaller adipocytes within adipose tissue, which correlated with the reduced adipogenesis observed in cultured ASCs harvested from these animals (J. H. Shin et al, , S. Shin, Seong, & Bae, ).…”
Section: Overview Of Recently Published Work In Ascsmentioning
confidence: 99%
“…Similar to Pin1, expression of the scaffolding protein Ahnak, which facilitates the Smad‐1 signaling required to induce PPARγ2 expression during adipogenesis, is also elevated in obesity and is upregulated during adipogenesis (J. Li, Yu, Pan, & Unger, ; J. H. Shin et al, ). Ahnak KO mice exhibited decreased fat mass and smaller adipocytes within adipose tissue, which correlated with the reduced adipogenesis observed in cultured ASCs harvested from these animals (J. H. Shin et al, , S. Shin, Seong, & Bae, ).…”
Section: Overview Of Recently Published Work In Ascsmentioning
confidence: 99%